TRANSFORMATION OF PRODUCTION AND LABOR STRUCTURE IN THE ECONOMY OF CENTRAL JAVA PROVINCE - Alfin Bahtiar; Juliannus Johnny Sarungu (Journal of Applied Economics in Developing Countries, 2020)
The purpose of this study is: 1) Describe how much the contribution of the agricultural sector, manufacturing and services in the structure of production and employment 2) Describe the pattern of transformation of production structures in the economy 3) Describe the pattern of labor structure transformation in the economy, and 4) Describe the Base sectors in Central Java Province. This study uses data from the GDP and Labor in Central Java Province and Indonesia, which are grouped based on the agricultural sector, manufacturing and services. The analytical tool used in this study is Shift Share Analysis and Location Quotient (LQ) Analysis. The results of the analysis show that the production structure in 2010 - 2017, the agricultural, manufacturing, and services sector contribute positively to GDP. However, the contribution of the agricultural and manufacturing sectors is classified as weak, while the service sector is classified as strong. In the structure of labor, the contribution of the agricultural sector is also classified as weak, while the manufacturing sector and service sector are relatively strong in absorbing workers. The pattern of changes in production structure shows that the agricultural sector is negative. While the manufacturing sector and service sector always show positive values and tend to increase. The pattern of changes in the employment structure shows that the agricultural sector always decreases the number of workers. Whereas in the manufacturing sector tends to fluctuate, which in 2017 the value increases. Likewise with the service sector, which tends to fluctuate, and in 2017 there was the most significant increase in the number of workers. The agricultural and manufacturing sectors are the base sector and have comparative advantages in Central Java Province.Keywords: Economic structure transformation, GDP, labor, agricultural sector, manufacturing sector, service sector, base sector